Sintering and biocompatibility of blended elemental Ti-xNb alloys. (April 2020) - Chen, Yunhui; Han, Pingping; Dehghan-Manshadi, Ali; Kent, Damon; Ehtemam-Haghighi, Shima; Jowers, Casey; Bermingham, Michael; Li, Tong; Cooper-White, Justin; Dargusch, Matthew S.
Abstract: Titanium-niobium (Ti–Nb) alloys have great potential for biomedical applications due to their superior biocompatibility and mechanical properties that match closely to human bone. Powder metallurgy is an ideal technology for efficient manufacture of titanium alloys to generate net-shape, intricately featured and porous components. This work reports on the effects of Nb concentrations on sintered Ti-xNb alloys with the aim to establish an optimal composition in respect to mechanical and biological performances. Ti-xNb alloys with 33, 40, 56 and 66 wt% Nb were fabricated from elemental powders and the sintering response, mechanical properties, microstructures and biocompatibility assessed and compared to conventional commercial purity titanium (CPTi). The sintered densities for all Ti-xNb compositions were around 95%, reducing slightly with increasing Nb due to increasing open porosity. Higher Nb levels retarded sintering leading to more inhomogeneous phase and pore distributions. The compressive strength decreased with increasing Nb, while all Ti-xNb alloys displayed higher strengths than CPTi except the Ti–66Nb alloy. The Young's moduli of the Ti-xNb alloys with ≥40 wt% Nb were substantially lower (30–50%) than CPTi. In-vitro cell culture testing revealed excellent biocompatibility for all Ti-xNb alloys comparable or better than tissue culture plate and CPTi controls, with the Ti–40Nb alloy exhibiting superior cell-material interactions. In view of its mechanical and biological performance, the Ti–40Nb composition is most promising for hard tissue engineering applications. Graphical abstract: Image 1 Highlights: Investigation of Ti–Nb alloys across a wide (33-66 wt% Nb) composition range. Alloying with ≤56 wt% Nb gives higher (~30–120%) strength than CPTi. Alloying with ≥40 wt% Nb gives lower (~30–50%) Young's moduli than CPTi. In-vitro cell tests show superior cell interactions for Ti–40Nb (wt%) composition. Ti–40Nb (wt%) offers optimal combination of mechanical and biological performances.